ANALISIS HUBUNGAN TINGKAT KEBAHAGIAAN DENGAN KUALITAS LINGKUNGAN DAN PEMBANGUNAN TEKNOLOGI INFORMASI - Muhammad Rusyda; Tiodora Hadumaon Siagian (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2023)
Environmental pollution is a priority issue to be prevented and resolved. Environmental management must maintain the environmental balance so that environmental conditions can be maintained properly. A healthy environment will provide comfort in people's lives. On the other hand, the rapid development of information and communication technology (ICT) provides various conveniences in communicating, obtaining information, and accessing entertainment. However, these facilities can have a negative influence, such as reduced social interaction, increased information-based crime, etc. The question is whether a healthier living environment and the rapid development of ICT make people happier. This study tried to analyze the relationship between environmental quality and ICT development with happiness indices using panel data from 34 provinces in Indonesia. The method of analysis used is regression analysis. The results showed that environmental quality and ICT development positively affect happiness. These results conclude that to increase happiness, one can maintain the quality of the environment, such as by preventing and resolving air and water, and soil pollution. Then the positive side of information and communication technology must be continuously improved to provide more comprehensive benefits for society.